1996
DOI: 10.1074/jbc.271.39.23619
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Line-derived Neurotrophic Factor Signals through the RET Receptor and Activates Mitogen-activated Protein Kinase

Abstract: Glial cell line-derived neurotrophic factor (GDNF), a member of the transforming growth factor-beta family of growth factors, was first identified by its ability to promote the survival of midbrain dopaminergic neurons in culture. We demonstrate that GDNF treatment of several neuroblastoma cell lines leads to dose-dependent tyrosine phosphorylation of the RET receptor and that other transforming growth factor-beta family members are not able to activate the RET receptor. GDNF treatment of neuroblastoma cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 33 publications
5
67
1
1
Order By: Relevance
“…GDNF binding to RET receptor lead to tyrosine kinase autophosphorylation at a set of 16 cytoplasmic tyrosine residues, in the RET short and middle isoforms, and two additional tyrosines in the carboxy-terminal tail, in the RET long isoform. RET receptor tyrosine kinase autophosphorylation can activate various signaling pathways including RAS/ERK, PI3K/AKT and p38MAPK (Worby et al, 1996;Xing et al, 1998;Chiariello et al, 1998;Trupp et al, 1999;Soler et al, 1999;Hayashi et al, 2000;Takahashi, 2001;Sariola and Saarma, 2003). Particularly, it has been demonstrated that Tyr1062 is involved in the activation of Ras/Erk or PI3K/Akt pathways (Besset et al, 2000;Hayashi et al, 2000Hayashi et al, , 2001Murakami et al, 1999aMurakami et al, , 1999b and is required for GDNF-mediated neurons differentiation and survival (Coulpier et al, 2002;Califano et al, 2000;De Vita et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDNF binding to RET receptor lead to tyrosine kinase autophosphorylation at a set of 16 cytoplasmic tyrosine residues, in the RET short and middle isoforms, and two additional tyrosines in the carboxy-terminal tail, in the RET long isoform. RET receptor tyrosine kinase autophosphorylation can activate various signaling pathways including RAS/ERK, PI3K/AKT and p38MAPK (Worby et al, 1996;Xing et al, 1998;Chiariello et al, 1998;Trupp et al, 1999;Soler et al, 1999;Hayashi et al, 2000;Takahashi, 2001;Sariola and Saarma, 2003). Particularly, it has been demonstrated that Tyr1062 is involved in the activation of Ras/Erk or PI3K/Akt pathways (Besset et al, 2000;Hayashi et al, 2000Hayashi et al, , 2001Murakami et al, 1999aMurakami et al, , 1999b and is required for GDNF-mediated neurons differentiation and survival (Coulpier et al, 2002;Califano et al, 2000;De Vita et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…RET short and middle isoforms contain 16 tyrosine residues in their intracellular domains and RET long isoform has two additional tyrosines in the carboxy-terminal tail. Like other receptor tyrosine kinases, RET can activate different signaling pathways including Ras/Erk, PI3K/Akt, p38/MAPK, PLCg and c-Jun N-terminal kinase (JNK) (Worby et al, 1996;Xing et al, 1998;Chiariello et al, 1998;Trupp et al, 1999;Soler et al, 1999;Hayashi et al, 2000;Takahashi, 2001;Sariola and Saarma, 2003). Among the various tyrosine kinase of RET, it has been demonstrated that Tyr1062 is involved in the activation of Ras/Erk or PI3K/Akt pathways (Besset et al, 2000;Hayashi et al, 2000Hayashi et al, , 2001Murakami et al, 1999aMurakami et al, , 1999b and it is required for GDNF-mediated differentiation and survival of neurons (Coulpier et al, 2002;Califano et al, 2000;De Vita et al, 2000;Asai et al, 1996;Besset et al, 2000) As extension of previous work (Battaglia et al, 2009), in the present study we aimed to verify if the enhancement of GDNF production in mouse striatum following treatment with LY379268 may also induce in the nigrostriatal system a time-related activation of RET receptor and its specific intracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
“…These residues can serve as intracellular docking sites to many different SH2 domain-containing proteins, including Src. While Src interacts with Ret at Tyr 981 (Encinas et al, 2004), Tyr 1062 serves as a docking site to most other effectors and triggers the activation of the Ras signaling pathway in the developing enteric nervous system, the developing kidney, and also in neuroblastoma (Worby et al, 1996;Jijiwa et al, 2004;Hayashi et al, 2000). Therefore, we examined whether Gdnf can activate Ras signaling in SSCs (He et al, 2008).…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…Recently, however, the Ret tyrosine kinase protein was identified as the signal transducing component of the GDNF receptor complex (2)(3)(4)(5)(6). The association between Ret and GDNF was deduced in part from the phenotypic similarities of mice with null mutations for either the ligand or the receptor.…”
mentioning
confidence: 99%